Scientific progress without increasing verisimilitude: In response to Niiniluoto. (June 2015) - Rowbottom, Darrell P.
Abstract: First, I argue that scientific progress is possible in the absence of increasing verisimilitude in science's theories. Second, I argue that increasing theoretical verisimilitude is not the central, or primary, dimension of scientific progress. Third, I defend my previous argument that unjustified changes in scientific belief may be progressive. Fourth, I illustrate how false beliefs can promote scientific progress in ways that cannot be explicated by appeal to verisimilitude. Highlights: Shows that scientific progress can occur without science's theories increasing in verisimilitude. Argues that increasing theoretical verisimilitude is also not the central aspect of scientific progress. Urges that a central aspect of scientific progress is increasing predictive power and improving understanding of phenomena. Illustrates that false beliefs may promote scientific progress in ways not explicable by appeal to verisimilitude. Maintains that unjustified changes in scientific belief may be progressive.